AMINA BIOGENIK SEBAGAI INDIKATOR KEAMANAN PRODUK PANGAN - Pawestri, Setyaning; Syahbanu, Fathma; Syahidawati, Ahsanatun (Agros Journal of Agriculture Science, 2024)
The presence of biogenic amines in food products is a significant indicator of food safety. Consumption of biogenic amines in small quantities is not a problem, but consumption in high levels can endanger the health of consumers. The concentration of biogenic amines in food products is influenced by several factors in the production process, including initial microbial composition, raw material hygiene, fermentation conditions, and duration of fermentation. Biogenic amines can also be formed by the microbiological degradation of high-protein foods during the fermentation process. Two types of biogenic amines that are indicators most often used for safety are histamine and tyramine. Various cases of poisoning with these two substances have been reported, with histamine being associated with fishery product poisoning and tyramine being associated with cheese poisoning. The common methods used to detect biogenic amines are chromatography, such as GC, HPLC, and Thin Layer Chromatography (TLC). The purpose of this literature review is to discuss the phenomenon of the formation of biogenic amines in food products associated with aspects of food product quality, food safety, and methods for detecting the presence of biogenic amine compounds in food products. Keywords: biogenic amines, food safety, fermented food INTISARIKeberadaan amina biogenik pada produk pangan menjadi salah satu indikator keamanan makanan yang signifikan. Konsumsi amina biogenik dalam jumlah kecil tidak menjadi masalah, tetapi konsumsi dalam kadar tinggi dapat membahayakan kesehatan konsumen. Konsentrasi amina biogenik dalam produk pangan dipengaruhi oleh beberapa faktor dalam proses produksinya, diantaranya komposisi mikroba awal, higienitas bahan baku, kondisi fermentasi, dan lama waktu fermentasi. Amina biogenik juga dapat terbentuk oleh degradasi mikrobiologis dari makanan berprotein tinggi selama proses fermentasi. Dua jenis amina biogenik yang menjadi indikator paling sering digunakan untuk keamanan adalah histamin dan tiramin. Berbagai kasus terkait keracunan 2 zat ini telah dilaporkan, histamin dikaitkan dengan kasus keracunan produk perikanan dan tiramin dikaitkan dengan kasus keracunan keju. Metode yang umum digunakan untuk mendeteksi keberadaan amina biogenik ini yaitu kromatografi, seperti GC, HPLC, maupun kromatografi lapis tipis. Tujuan dari kajian literatur ini adalah membahas fenomena terjadinya pembentukan amina biogenik pada produk pangan dihubungkan dengan aspek kualitas produk pangan, keamanan pangan, serta metode deteksi keberadaan senyawa amina biogenik pada produk pangan. Kata kunci: amina biogenik, produk pangan, keamanan pangan